Unlocking potential: low frequency subthalamic nucleus stimulation enhances executive function in Parkinson’s disease patients with postural instability/gait disturbance - Qin, Guofan; Xie, Hutao; Shi, Lin; Zhao, Baotian; Gan, Yifei; Yin, Zixiao; Xu, Yichen; Zhang, Xin; Chen, Yaojing; Jiang, Yin; Zhang, Quan; Zhang, Jianguo (Frontiers in Neuroscience, 2023)
Postural instability/gait disturbance (PIGD) is very common in advanced Parkinson’s disease, and associated with cognitive dysfunction. Research suggests that low frequency (5–12 Hz) subthalamic nucleus-deep brain stimulation (STN-DBS) could improve cognition in patients with Parkinson’s disease (PD). However, the clinical effectiveness of low frequency stimulation in PIGD patients has not been explored. This study was designed in a double-blinded randomized cross-over manner, aimed to verify the effect of low frequency STN-DBS on cognition of PIGD patients. Twenty-nine PIGD patients with STN-DBS were tested for cognitive at off (no stimulation), low frequency (5 Hz), and high frequency (130 Hz) stimulation. Neuropsychological tests included the Stroop Color-Word Test (SCWT), Verbal fluency test, Symbol Digital Switch Test, Digital Span Test, and Benton Judgment of Line Orientation test. For conflict resolution of executive function, low frequency stimulation significantly decreased the completion time of SCWT-C (p = 0.001) and Stroop interference effect (p < 0.001) compared to high frequency stimulation. However, no significant differences among stimulation states were found for other cognitive tests. Here we show, low frequency STN-DBS improved conflict resolution of executive function compared to high frequency. Our results demonstrated the possibility of expanding the treatment coverage of DBS to cognitive function in PIGD, which will facilitate integration of low frequency stimulation into future DBS programming.